Overview of molecular mechanisms of plant leaf development: a systematic review - Lv, Zhuo; Zhao, Wanqi; Kong, Shuxin; Li, Long; Lin, Shuyan (Frontiers in Plant Science, 2023)
Leaf growth initiates in the peripheral region of the meristem at the apex of the stem, eventually forming flat structures. Leaves are pivotal organs in plants, serving as the primary sites for photosynthesis, respiration, and transpiration. Their development is intricately governed by complex regulatory networks. Leaf development encompasses five processes: the leaf primordium initiation, the leaf polarity establishment, leaf size expansion, shaping of leaf, and leaf senescence. The leaf primordia starts from the side of the growth cone at the apex of the stem. Under the precise regulation of a series of genes, the leaf primordia establishes adaxial-abaxial axes, proximal-distal axes and medio-lateral axes polarity, guides the primordia cells to divide and differentiate in a specific direction, and finally develops into leaves of a certain shape and size. Leaf senescence is a kind of programmed cell death that occurs in plants, and as it is the last stage of leaf development. Each of these processes is meticulously coordinated through the intricate interplay among transcriptional regulatory factors, microRNAs, and plant hormones. This review is dedicated to examining the regulatory influences of major regulatory factors and plant hormones on these five developmental aspects of leaves.